Beyond corporate image: projecting international reputation management as a new theoretical approach in a transitional country - Abdullah, Zulhamri (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This paper seeks to build a theoretical approach to international reputation management from the perspective of strategic management and multiculturalism. Collective ideas and arguments are undertaken based on literature reviews of public relations, corporate communication, strategic management and cultural diversity. This paper has proposed an adaptive model of international reputation management based on realistic communication practice in a transitional country. This model seems unique in terms of localisation is focused to reiterate an international perspective beyond western philosophy. In the 21st century, the world has changed tremendously and so has the way global corporations operate their business in fast developing countries. Image alone is not enough to build a favourable reputation of corporations. Reputation management, a new and emerging function of corporate communication, is being used as strategic tactical and managerial roles within an organisation. This paper may benefit global corporations operating in a transitional country in how they may foster and maintain their business by focusing on ‘glocalisation’ instead of infusing their pure western philosophy.